A chaotic jerk system with three cubic nonlinearities, dynamical analysis, adaptive chaos synchronization and circuit simulation - Mustafa, M.; Vaidyanathan, S.; Sambas, A.; Zhang, S.; Mujiartob, .; Subiyanto, . (2019)
A 3-D new chaotic jerk system with three cubic nonlinearities is proposed in this paper. The dynamical properties of the new jerk system are described in terms of phase portraits, Lyapunov exponents, Kaplan-Yorke dimension, symmetry, dissipativity, etc. Also, a detailed dynamical analysis of the jerk system has been carried out with bifurcation diagram and Lyapunov exponents. As an engineering application, adaptive synchronization of the new chaotic jerk system with itself is designed via backstepping control method. Furthermore, an electronic circuit realization of the new chaotic jerk system is presented in detail to confirm the feasibility of the theoretical chaotic jerk mode.